APLIKASI MEMBRAN DALAM PEMEKATAN ENZIM GLUKOAMILASE - A. Syahril; S Nana; L. Z. Udin; A. Sidik; A. T. Karossi (Jurnal Kimia Terapan Indonesia, 1993)
Preparation of glucoamylase enzyme by fermentation of sago and soy bean meals had been done. Enzyme concentration was carried out by ultrafiltration process, where polysulfone membranes were used as medium filter. Membranes used in this experiment were prepared with several treatments, such as coagulation temperature and composition and beside that effect of solvent and additive are also observed. From the results of the observation during fermentation process in enzyme preparation, its clear that pH of solution changed in that pH increased with increasing fermentation time. The highest enzyme activity was shown on the sixth day of fermentation namely 2.908 U/ml with a specific enzyme activity of 1495.8 U/g protein. There is fluctuation in protein content during [ermenuuion process, but the highest level was obtained on the tenth day [ermenuuion (3.102 mg/l). The highest specific enzyme activity was shown on the sixth day fermentation (1495.8 U1g protein). The best membrane for the enzyme concentration by ultrafiltration process in this experiment are found form the membrane prepared from dimethyl acetamide as solvent and polyvinylpyrrolidane as additive. This membrane gave rejection coefficient of more than 90% andflux as much as 20.571 l/m2.hour.